Disseminating cycling knowledge. - (:unkn) unknown (My University, 2013)
Broad-based knowledge transfer is one of the central success factors of cycling promotion in Germany. The established and offered formats make information about best practices accessible locally in a decentralised fashion. They also help stakeholders to stay on top of the ever-increasing body of knowledge in the field of cycling. (Difu)
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Kommunikation; Öffentlichkeitsarbeit; Radverkehrskampagne; Kampagne; Good Practice; Radverkehrsplan